IMPLEMENTATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE ACTIVITIES OF PUBLIC AUTHORITIES OF DEVELOPING COUNTRIES: EXPERIENCE FOR UKRAINE - Fisenko, N. (Theory and Practice of Public Administration, 2020)
The success of public sector reforms, the implementation of e-government and the stability of its functioning depend on many factors that differ from country to country. From a theoretical point of view, the most thorough analysis of the problems of the development of developing countries was made within the framework of post-colonial theory and the theory of constructivism in international relations. They provided the impetus for the development of existing institutional and historical-structural approaches that could form the basis for developing effective development strategies. They include a reassessment of the goals and functions of donors in ICT development projects, a greater focus on internal forces that drive the growth of institutional and political stability, human resources, relations between reform actors, including the establishment of an effective partnership, and so on. Thus, post-colonial theory and an adaptive approach provide a productive alternative to idealistic theories and concepts and provide a strong theoretical ground for public sector reforms, in particular in the context of implementing modern ICT. They also help to create a legitimate basis for implementing appropriate reforms and strategies in developing countries. At the same time, they do not solve all problems, but only increase the adaptability of Western projects to local realities, taking into account the existing system of values, experience, traditions, objective assessment of available human, financial, organizational and other resources.